Intermittent Bolus versus Continuous Infusion of Propofol for Deep Sedation during ABR/Nuclear Medicine Studies - Ahmed, Sheikh Sohail; Hicks, Shawn; Slaven, James E.; Nitu, Mara (Journal of Pediatric Intensive Care, 2017)
Objective A comparison of intermittent bolus (IB) versus continuous infusion of propofol for deep sedation.Material and Methods A retrospective review of patients sedated for Auditory Brainstem Response (ABR)/nuclear medicine studies between September 2008 and February 2015. A ketamine bolus (0.5 mg/kg < 20 kg, 0.25 mg/kg > 20 kg) followed by propofol bolus of 1 mg/kg over 2 minutes. In the IB group, maintenance of deep sedation was with incremental bolus of 10 to 20 mg of propofol. In continuous infusion group (CG), maintenance was with a continuous infusion of 83 mcg/kg/min of propofol.Results Of the 326 cases completed, 181 were in CG group and 145 were in IB group. There were no statistical differences in patient's age, weight, and American Society of Anesthesiologist (ASA) classification. The cardiovascular and respiratory parameters in the two groups were not different statistically. Mean total propofol dose was higher in CG group versus IB group (CG 7.6 mg ± 3.6 mg, IB 6.5 mg ± 3.6 mg; p = 0.008). Procedure time in CG group was longer by 8 minutes compared with IB group (CG 49.8 min ± 25.4 min versus 42.3 min ± 19.2 min; p = .003). CG group has both shorter recovery time (CG 8.1 min ± 4.7 min versus IB 10.0 min ± 8.5 min; p = 0.01) and discharge time.Conclusion Satisfactory sedation and completion of the procedure was accomplished with both sedation protocols.
Keywords: deep sedation; incremental bolus; continuous infusion